DRCSF 2020
DOI: 10.37281/drcsf/1.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of various soil cultivation methods on some microbial soil properties

Abstract: Cultivating the top 0-25 cm soil layer by ploughing cultivating method requires considerable energy, labor, and additional costs. Also, the larger soil surface caused by cultivation, the moisture content of soil can be lost easier. Therefore, in recent years soil loosening cultivation has become gained popularity, particularly to protect the moisture content of soil and reduce the risk of desertification. At the Experimental Station of Debrecen University, known as Látókép (a name, which corresponds approximat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…However, increased temperature might be expected to increase rates of SOM turnover in temperate climates if water availability is sufficient (Bond-Lamberty and Thomson 2010;Bond-Lamberty et al 2018;Chen et al 2020), resulting in decreased soil C sequestration. In addition, climate change can increase growing season length and, in the absence of nutrient or water limitation (Sándor et al 2020;Kocsis et al 2018), can enhance biomass and litter production. An assumption built into many ecosystem models is that such increases in detrital inputs will also increase soil C sequestration, although the extent of the link and, in some cases, the direction of the relationship between litter inputs and soil C sequestration has recently come into question (Bowden et al 2014;Fekete et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…However, increased temperature might be expected to increase rates of SOM turnover in temperate climates if water availability is sufficient (Bond-Lamberty and Thomson 2010;Bond-Lamberty et al 2018;Chen et al 2020), resulting in decreased soil C sequestration. In addition, climate change can increase growing season length and, in the absence of nutrient or water limitation (Sándor et al 2020;Kocsis et al 2018), can enhance biomass and litter production. An assumption built into many ecosystem models is that such increases in detrital inputs will also increase soil C sequestration, although the extent of the link and, in some cases, the direction of the relationship between litter inputs and soil C sequestration has recently come into question (Bowden et al 2014;Fekete et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Protection of soil quality is a pillar of sustainable development [1][2][3] . Recent studies considered effects of minerals [4][5][6] and soil cultivation techniques 7,8 on soil quality and soil microbial activity [9][10][11][12] . These studies reported interactions between soil minerals and decomposition of organic matter; positive correlations between soil microbial activity (measured by number of bacteria and fungi, soil respiration, and C and N cycle-related enzyme activity) and cultivation methods, and fertilizer usage.…”
Section: Introductionmentioning
confidence: 99%
“…Among processes to be monitored, decomposition of organic matter is of primary significance 17 , considering that this process is strongly influenced by soil microbiological activity. Soil management is another research area of increasing interest 18 owing to its significance in soil microbial activity 19 that can be expressed by enzymatic activity, soil respiration, and MBC 11 . Local farmers have demonstrated willingness to start permaculture systems involving tropical orchards, like those previously operated successfully in another plant, Guayusa (Ilex guayusa) 20 , in the Amazon region.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several studies have been undertaken on the effects on soil quality exerted by various minerals contained in the soil, such as ammonium lactate-soluble potassium and phosphorus content (Jakab, 2020;Li et al, 2020). Also investigated was the impact of various soil cultivation methods on some microbial soil properties (Beni et al, 2017;Sándor et al, 2020;Sándor, 2020;Veres et al, 2015).…”
Section: Introductionmentioning
confidence: 99%